2019
DOI: 10.1016/j.cois.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular bases of sensory processes in kissing bugs, vectors of Chagas disease

Abstract: Sensory processes represent an information gathering interface between animals and their surrounding world. Therefore, they serve to scan the environment for resources and threats.The behavior of kissing bugs has been studied to aid their control because they transmit Chagas disease to humans. Besides, a few triatomines represent important insect models since Wigglesworth times. These hematophagous insects rely on different sensory systems to scan their environment for blood-sources, mating partners and hiding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Molecular characterization of the pharyngeal organ of insects is scarce, however, this was performed for D. melanogaster in a more recent study which the expression of bitter and sugar GRs in the pharyngeal GRNs was reported, among other genes (Chen and Dakanukar, 2017). Among the repertoire of expressed GRs of R. prolixus , only RproGr1 shows homology to DmelGr43a , which functions as a fructose receptor that triggers satiety responses once high fructose levels are detected (Miyamoto et al, 2012; Latorre-Estivalis and Lorenzo, 2019). Interestingly, DmelGr43a , which is expressed in a few neurons in the protocerebrum, appears to be restricted to some pharyngeal and tarsal GRNs in the fly gustatory system (LeDue et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular characterization of the pharyngeal organ of insects is scarce, however, this was performed for D. melanogaster in a more recent study which the expression of bitter and sugar GRs in the pharyngeal GRNs was reported, among other genes (Chen and Dakanukar, 2017). Among the repertoire of expressed GRs of R. prolixus , only RproGr1 shows homology to DmelGr43a , which functions as a fructose receptor that triggers satiety responses once high fructose levels are detected (Miyamoto et al, 2012; Latorre-Estivalis and Lorenzo, 2019). Interestingly, DmelGr43a , which is expressed in a few neurons in the protocerebrum, appears to be restricted to some pharyngeal and tarsal GRNs in the fly gustatory system (LeDue et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of tastants that activate each of the different taste receptor proteins in different body parts are available for D. melanogaster adults ( Chen and Dahanukar 2020 ). A search for genes similar to those that encode these receptors has begun in other insect species (e.g., Sparks and Dickens 2017 , Latorre-Estivalis and Lorenzo 2019 , Xu 2020 ). A small subset of these studies have also assessed what body parts these receptors are expressed on and what tastants the receptors bind to.…”
Section: The Location Of ‘Taste Receptor Molecules’ and The Definitio...mentioning
confidence: 99%
“… 34 , 35 Extensive long-term efforts toward decoding the sensory ecology of triatomines 30 , 36 , 37 have identified olfactory, thermal, and environmentally mediated cues as well as the neuroethology underlying its complex host-seeking behavior. 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 Moreover, the annotated R. prolixus genome 36 and recent transcriptomic studies 45 , 46 , 47 provide detailed profiles of candidate sensory receptor genes, including olfactory, ionotropic, pickpocket, and TRP receptors that can be used to probe the genetic basis of sensory traits. 48 , 49 …”
Section: Introductionmentioning
confidence: 99%